Best Practice Guidelines for the Use of Next‐Generation Sequencing Applications in Genome Diagnostics: A National Collaborative Study of Dutch Genome Diagnostic Laboratories. Issue 10 (19th August 2013) - Weiss, Marjan M.; Van der, Bert; Jongbloed, Jan D. H.; Vogel, Maartje J.; Brüggenwirth, Hennie T.; Lekanne Deprez, Ronald H.; Mook, Olaf; Ruivenkamp, Claudia A. L.; van, Marjon A.; van den, Arthur; Waisfisz, Quinten; Nelen, Marcel R.; et al.
ABSTRACT Next‐generation sequencing (NGS) methods are being adopted by genome diagnostics laboratories worldwide. However, implementing NGS‐based tests according to diagnostic standards is a challenge for individual laboratories. To facilitate the implementation of NGS in Dutch laboratories, the Dutch Society for Clinical Genetic Laboratory Diagnostics (VKGL) set up a working group in 2012. The results of their discussions are presented here. We provide best practice guidelines and criteria for implementing and validating NGS applications in a clinical setting. We introduce the concept of "diagnostic yield" as the main performance characteristic for evaluating diagnostic tests. We recommend that the laboratory procedures, including the tested genes, should be recorded in a publicly available document describing the complete "diagnostic routing." We also propose that laboratories should use a list of "core disease genes" for specific genetic diseases. This core list contains the essential genes for each disease, and they should all be included in a diagnostic test to establish a reliable and accurate molecular diagnosis. The guidelines will ensure a clear and standardized quality of care provided by genetic diagnostic laboratories. The best practice guidelines and criteria that are presented here were adopted by the VKGL in January 2013.